2011
DOI: 10.1007/s10071-011-0468-4
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys (Macaca mulatta) show robust evidence for memory awareness across multiple generalization tests

Abstract: The possibility that memory awareness occurs in nonhuman animals has been evaluated by providing opportunity to decline memory tests. Current evidence suggests that rhesus monkeys (Macaca mulatta) selectively decline tests when memory is weak (Hampton, 2001; Smith, Shields, & Washburn, 2003). (R.R. Hampton, 2001; Smith, Shields, & Washburn, 2003). However, much of the existing research in nonhuman metacognition is subject to the criticism that, after considerable training on one test type, subjects learn to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…The third test manipulated the stimulus brightness and stimulus duration simultaneously in order to change task difficulty. The aim of the Test 3 was to control for novelty effects and to confirm that the use of the Repeat key really depended on the difficulty of the trial (Templer and Hampton 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The third test manipulated the stimulus brightness and stimulus duration simultaneously in order to change task difficulty. The aim of the Test 3 was to control for novelty effects and to confirm that the use of the Repeat key really depended on the difficulty of the trial (Templer and Hampton 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Yet again, humans ( Figure 2A) and monkeys ( Figure 2B) displayed an increase in the use of the UR corresponding with a decrease in use of the categorization responses for the most difficult trials. Other experiments explored metacognition in rhesus monkeys and showed that the use of the UR or other metacognitive responses transfers across a variety of different tasks (Basile, Schroeder, Brown, Templer, & Hampton, 2015;Brown, Templer, & Hampton, 2017;Kornell, Son, & Terrace, 2007;Smith, Redford, Beran, & Washburn, 2010;Templer & Hampton, 2012) and that monkeys will continue using the UR when feedback is delayed (Smith, Beran, Redford, & Washburn, 2006), minimizing the likelihood that task-specific environmental cues are responsible for the use of the UR. Figure 1. A.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
“…Thus, the macaques reported uncertainty in their recall under conditions in which no single environmental stimulus could easily cue the UR response and when the likelihood of correctly responding on the task was small. Templer and Hampton (2012) also presented rhesus monkeys with a set of memory tasks and found that the monkeys were consistently more accurate on trials where they could have avoided answering the primary question than on trials where they were forced to answer it. And, the monkeys adjusted their use of trial declining responses depending on whether the various tasks made it easier or harder to remember stimuli.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
“…Animals cannot easily report their confidence in these ways. However, rhesus monkeys and rats can provide other responses that reflect the monitoring of uncertainty of their perceptual experiences (Beran, Smith, Redford, & Washburn, 2006; Foote & Crystal, 2007, 2012; Shields, Smith, & Washburn, 1997; Smith, Beran, Redford, & Washburn, 2006; Smith, Redford, Beran, & Washburn, 2010; Smith, Schull, Strote, McGee, Egnor, & Erb, 1995; Smith, Shields, Schull, & Washburn, 1997) and pigeons, rhesus monkeys, and orangutans provide responses that reflect monitoring of memory (Adams & Santi, 2011; Basile, Hampton, Suomi, & Murray, 2009; Fujita, 2009; Hampton, 2001; Hampton & Hampstead, 2006; Inman & Shettleworth, 1999; Smith, Shields, Allendoerfer, & Washburn, 1998; Suda-King, 2008; Suda-King, Bania, Stromberg, & Subiaul, 2013; Sutton & Shettleworth, 2008; Templer & Hampton, 2012). Rhesus monkeys, chimpanzees, orangutans, and pigeons have demonstrated the ability to search for needed information (Beran & Smith, 2011; Beran, Smith, & Perdue, 2013; Call, 2010; Call & Carpenter, 2001; Castro & Wasserman, 2013; Hampton, Zivin, & Murray, 2004; Iwasaki, Watanabe, & Fujita, 2013; Kirk, McMillan, & Roberts, 2014; Marsh & MacDonald, 2012a, 2012b; Roberts et al, 2009), and have even shown the capacity to make confidence judgments about the outcomes of already completed responses, although only with extensive training (Kornell, Son, & Terrace, 2007; Morgan, Kornell, Kornblum, & Terrace, 2014; Nakamura, Watanabe, Betsuyaku, & Fujita, 2011; Shields, Smith, Guttmannova, & Washburn, 2005).…”
mentioning
confidence: 99%